Okrogle lezije v dojki - Vargazon, Tomaž (Radiology and oncology (Ljubljana), 1998)
The article describes the characteristics of well-defined breasts lesions as well as their differential diagnostics. The author of this article tries refreshens the role of radiologist and the significance of radiologic diagnostics, ultrasound and other interventions in the breast. Sometimes, onlymammography is enough to establish final diagnosis. The majority of oval breasts lesions, visible on standard mammograms have to be additionaly diagnostically treated; however the surgical biopsy of well-defined oval tumors is seldom made.
Keywords: anatomija; Breast diseases; Diagnosis; Diagnosis, differential; diagnostika; dojke; Mammography; mamografija; novotvorbe; Radiography, interventional; Ultrasonography